KANO STATE COMMERCIAL BOTANICAL GARDENS: ETHNOBOTANICAL SURVEY OF MEDICINAL PLANTS GROWN THEREIN FOR THE TREATMENT OF VARIOUS HUMAN AILMENTS (FUDMA JOURNAL OF SCIENCES, 2025)
Kano state metropolis is rich in botanical gardens operated by non-governmental bodies which are mostly located along the roadside. Their services are not limited to buying and selling of ornamental plants but also growing medicinal plants for herbal medicine. This study was undertaken to identify medicinal plants in commercial botanical gardens of Kano metropolis as well as to document their medicinal practices by the inhabitants of the study area. Various botanical gardens were identified by snowball sampling and the respondents provided information via a semi-structured questionnaire. A total of 55 respondents participated in this study and most of them fall between the age of 21-30 years. They divulged the use of 53 medicinal plants in herbal medicine. The plants were reported to be used in the treatments 21 disease conditions including typhoid, malaria, hypertension, infection, pile, skin diseases etc. The plants with highest frequency index include Mangifera indica, Psidium guajaba, Senna siamae, Eucalyptus camaldulensis, Dodonaea viscosa, Musa paradisiaca, Syzygium cumini, Moringa oleifera Lam, Carica papaya, Acalypha wilkesiana, Citrus limon and Terminalia catappa. In addition, most of the medicinal plants in the gardens were found to be exotic plants (62%) and are grown for ornamental purposes (35 plants). Decoction and oral administration were the most mentioned method of preparation and administration respectively. Growing of our indigenous plants in the gardens is recommended for their conservation and sustainable development.
Keywords: Botanical gardens; Herbal medicine; Medicinal plants; Kano state metropolis